Odd interlude [compact disc, unabridged]. - Koontz, Dean R. (Dean Ray), 1945- (Koontz, Dean R. (Dean Ray), 1945- Odd Thomas novel., 2012)
Nestled on a lonely stretch along the Pacific coast, quaint roadside outpost Harmony Corner offers everything a weary traveler needs. But when Odd Thomas and company stop to spend the night, they discover that there's more to this secluded haven than meets the eye.